HEART BIRTH DEFECTS: DIAGNOSTIC AND THERAPEUTIC EXPERIENCE IN UZBEKISTAN - Niyozova Gulyor Davlat qizi (Web of Journals Publishing, 2024)
This article explores the diagnostic and therapeutic approaches to heart birth defects in Uzbekistan. It highlights the advancements, challenges, and outcomes observed in the clinical management of congenital heart defects (CHDs). By analyzing national health data and specific case studies, the paper identifies key trends and proposes strategies to improve early detection and treatment outcomes.
Keywords: Congenital heart defects, diagnostics, therapy, Uzbekistan, pediatric cardiology, healthcare.